Taxonomic revision of Clinacanthus (Acanthaceae) in Thailand - Bongcheewin, Bhanubong; Darbyshire, Iain; Satitpatipan, Veena; Kongsawadworakul, Panida (Phytotaxa, 2019)
The taxonomy of Clinacanthus in Thailand is revised. Nomenclature, descriptions and a key to the species are provided. Clinacanthus nutans is lectotypified. Clinacanthus burmanni var. robinsoni from Vietnam is found to be distinct from both C. nutans and C. siamensis and is elevated to species status.